Kajian Stilistika Semantik pada Ungkapan Bahasa Jawa Postingan Instagram @Gojekgentho - Arliva Ristiningrum; FX. Sawardi; Supana Supana (Departement of Mathematics Education, 2023)
Language style is one aspect that beautifies a language. The aims of this study are (1) to describe the forms of expression contained in uploads to the Instagram account @gojekgentho, (2) to describe the stylistics or language style of expressions in uploads to the Instagram account @gojekgentho. The object of this research is the expression uploaded by the Instagram account @gojekgentho. The source of the data in this research is the utterances in the Black and White television program on Trans7 in August 2011. This research uses library and note-taking techniques. The results of this study indicate (1) the form of expression in the Instagram account @gojekgentho, namely found 58 data, (2) of the 58 data found there were 13 data entered from several styles of language or figure of speech, namely (a) figure of speech assonance, (b) figure of speech pleonasm , (c) simile, (d) hyperbole. From all the expressions uploaded to the account, there is the same form in the rhyme